Potential drug-drug interaction of olverembatinib (HQP1351) using physiologically based pharmacokinetic models - Yu, Zhiheng; Lei, Zihan; Yao, Xueting; Wang, Hengbang; Zhang, Miao; Hou, Zhe; Li, Yafen; Zhao, Yangyu; Li, Haiyan; Liu, Dongyang; Zhai, Yifan (Frontiers in Pharmacology, 2022)
Olverembatinib (HQP1351) is a third-generation BCR-ABL tyrosine kinase inhibitor (TKI) for the treatment of T315I mutant chronic myelogenous leukemia (CML), exhibits drug-drug interaction (DDI) potential through cytochrome P450 (CYP) enzymes CYP3A4, CYP2C9, CYP2C19, CYP1A2, and CYP2B6. A physiologically based pharmacokinetic (PBPK) model was developed based on physicochemical and in vitro parameters, as well as clinical data to predict: (1) potential DDI between olverembatinib and CYP3A4 and CYP2C9 inhibitors or inducers, (2) the effect of olverembatinib on the exposure of CYP1A2, CYP2B6, CYP2C9, CYP2C19, and CYP3A4 substrates, and (3) pharmacokinetics in patients with liver function injury. The PBPK model successfully described the observed plasma concentrations of olverembatinib from healthy subjects and patients with CML after a single administration, and predicted olverembatinib exposure changes when coadministered with itraconazole (CYP3A4 strong inhibitor) and rifampicin (CYP3A4 strong inducer) which was validated by observed data. The predicted results suggest: (1) strong, moderate, and mild CYP3A4 inhibitors (which have some overlap with CYP2C9 inhibitors) may increase olverembatinib exposure by approximately 2.39-, 1.80- to 2.39-, and 1.08-fold, respectively; strong, and moderate CYP3A4 inducers may decrease olverembatinib exposure by approximately 0.29-, and 0.35- to 0.56-fold, respectively; (2) olverembatinib, as a perpetrator, would have none or limited impact on CYP1A2, CYP2B6, CYP2C9, CYP2C19, and CYP3A4 enzyme activity ; (3) the exposure of olverembatinib in liver function injury with Child-Pugh A, B, C may increase by 1.22-, 1.79-, and 2.13-fold, respectively. The simulations informed DDI risk for olverembatinib as a victim and perpetrator, and support olverembatinib label dose recommendations.